Polyp dimorphism in the Mediterranean Red Coral Corallium rubrum: siphonozooids are precursors to autozooids - Loentgen, Guillaume; Parks, Scott K.; Allemand, Denis; Tambutté, Sylvie; Ganot, Philippe (Frontiers in Marine Science, 2025)
Polyp dimorphism, the presence of distinct autozooid (feeding) and siphonozooid (water circulation) polyps, has evolved multiple times within octocorals (class Octocorallia). Traditional anatomical descriptions have been limited to early hand-drawn publications. In precious corals (family Coralliidae), polyp dimorphism has been documented in the pacific species such as Corallium japonicum, Pleurocorallium elatius and Pleurocorallium konojoi, over the past century, yet in the Mediterranean red coral, Corallium rubrum, the literature has consistently referred to these structures generically as “polyps”, neglecting the putative dimorphism and their respective roles in reproduction, growth, and development. A key distinction between red coral species lies in their reproductive strategies: Pacific species are broadcast spawners, with gametes developing in siphonozooids, while C. rubrum is a larval brooder, with gametes maturing in autozooids. In this study, we utilized laboratory-cultured C. rubrum and a custom video imaging system to document colony growth over extended time periods. Through histological analyses and long-term observations, we demonstrated that siphonozooids, previously thought to have purely structural roles, are precursors to autozooids, suggesting a novel mechanism for colony growth in C. rubrum. This finding has important implications for understanding the extraordinary lifespan of precious coral colonies, contributing a broader knowledge to octocoral biology.